2012
DOI: 10.1088/0957-4484/23/34/344009
|View full text |Cite
|
Sign up to set email alerts
|

Near-ultraviolet zinc oxide nanowire sensor using low temperature hydrothermal growth

Abstract: Two near-ultraviolet (UV) sensors based on solution-grown zinc oxide (ZnO) nanowires (NWs) which are only sensitive to photo-excitation at or below 400 nm wavelength have been fabricated and characterized. Both devices keep all processing steps, including nanowire growth, under 100 °C for compatibility with a wide variety of substrates. The first device type uses a single optical lithography step process to allow simultaneous in situ horizontal NW growth from solution and creation of symmetric ohmic contacts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 43 publications
3
15
0
Order By: Relevance
“…6 One particular advantage of ZnO nanowires is that it is a low-cost material that can be solution-synthesized on a vast variety of substrates. [7][8][9] A giant photoconductive gain of 10 8 leading to very high detector responsivity has been reported in single nanowire ZnO photodetectors and attributed to hole trapping at the nanowire surface due to oxygen chemisorption. 10 It has been demonstrated that the nanowire surface passivation allows to reach high detectivity values, while maintaining high responsivity of the detector.…”
Section: Introductionmentioning
confidence: 99%
“…6 One particular advantage of ZnO nanowires is that it is a low-cost material that can be solution-synthesized on a vast variety of substrates. [7][8][9] A giant photoconductive gain of 10 8 leading to very high detector responsivity has been reported in single nanowire ZnO photodetectors and attributed to hole trapping at the nanowire surface due to oxygen chemisorption. 10 It has been demonstrated that the nanowire surface passivation allows to reach high detectivity values, while maintaining high responsivity of the detector.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated the synthesis of zinc oxide nanowires (ZnO NWs) by using FEF method. ZnO NWs are one of the most useful 1D nanomaterials for a variety of applications including photodetection, light‐emitting diode, photocatalyst, piezoelectric energy conversion, photovoltaic energy conversion, and field effect transistor . Furthermore, the protocols for low‐temperature hydrothermal synthesis of ZnO NWs are quite well‐established .…”
mentioning
confidence: 99%
“…As the bias voltage was increased from 10 V to 15 V, the on/off ratio was gradually increased from 17.9 to 77.4. Furthermore, the decay time was dramatically decreased at the applied bias voltage of 15 V. For analyzing the recovery characteristics, the reset time ( τ ) is considered by I = ( I max – I dark ) e – t / τ , where I max and I dark are the dark and maximum current 12. In fact, the transient curves of the 1D single ZnO‐based photodetectors have exhibited two‐ or three‐order exponential decay nature 2, 8.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the photogenerated electron–hole pairs and desorption of oxygen molecules in 1D ZnO nanostructures contribute to the electron–hole pairs at the surface during UV illumination, which induces a photoconductivity 7–9. Accordingly, many studies have been focused on the fabrication and characterization of 1D ZnO nanostructure‐based UV photodetectors by using the chemical vapor deposition (CVD), vapor–liquid–solid process, and hydrothermal synthesis method 10–12. In order to form semiconductor–metal contacts, however, a somewhat complicated process and accurate control for the connections between the metal electrodes have been required until now.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation